Di-mu-azido-kappa N-4(1):N-1-bis[(1,10-phenanthroline-kappa N-2,N `)(thiocyanato-kappa N)lead(II)] - Mohammadnezhad, G.; Ghanbarpour, A.R.; Amini, M.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the centrosymmetric binuclear title compound, [Pb-2(N-3)(2)-( NCS)(2)(C12H8N2)(4)], the N-donor atoms of one N-heterocycle and the N-donor atom of a thiocyanate anion along with the sterically active lone-pair electrons comprise an approximate square; a plane through three atoms of this square is twisted slightly with respect to the square made up of the other four atoms (two from the other N-heterocycle and one each from the bridging azide anions) at a dihedral angle of 18.7 (1)degrees. The Pb-TT atom is in a Psi-square-antiprismaic coordination.